The intermembrane space protein Mix23 is a novel stress-induced mitochondrial import factor - Zöller, Eva (J Biol Chem, 2020)
The biogenesis of mitochondria requires the import of hundreds of precursor proteins. These proteins are transported post-translationally with the help of chaperones, meaning that the overproduction of mitochondrial proteins or the limited availability of chaperones can lead to the accumulation of cytosolic precursor proteins. This imposes a severe challenge to cytosolic proteostasis and triggers a specific transcription program called the mitoprotein-induced stress response, which activates the proteasome system. This coincides with the repression of mitochondrial proteins, including many proteins of the intermembrane space. In contrast, herein we report that the so-far-uncharacterized intermembrane space protein Mix23 is considerably up-regulated when mitochondrial import is perturbed. Mix23 is evolutionarily conserved and a homolog of the human protein CCDC58. We found that, like the subunits of the proteasome, Mix23 is under control of the transcription factor Rpn4. It is imported into mitochondria by the mitochondrial disulfide relay. Mix23 is critical for the efficient import of proteins into the mitochondrial matrix, particularly if the function of the translocase of the inner membrane 23 is compromised such as in temperature-sensitive mutants of Tim17. Our observations identify Mix23 as a novel regulator or stabilizer of the mitochondrial protein import machinery that is specifically up-regulated upon mitoprotein-induced stress conditions.